Primeira página
/
Matemática
/
Which equation is equivalent to 12sqrt [3](x+15)=36 sqrt [3](x+15)=3 x+15=9 x+15=-6 sqrt [3](x+15)=24

Pergunta

Which equation is equivalent to 12sqrt [3](x+15)=36
sqrt [3](x+15)=3
x+15=9
x+15=-6
sqrt [3](x+15)=24

Which equation is equivalent to 12sqrt [3](x+15)=36 sqrt [3](x+15)=3 x+15=9 x+15=-6 sqrt [3](x+15)=24

Solução

expert verifiedVerification of experts
4.7243 Voting
avatar
Beatriz MariaMestre · Tutor por 5 anos

Responder

Divide both sides by$12$ <br />$\sqrt[3]{x+15}=3$ <br />
Clique para avaliar: